The communication effects of sponsorship in local sports markets - Sławomir Kowalski (Nicolaus Copernicus University in Toruń, 2016)
Local sports market depends on the groups of stakeholders. One of them are the sponsors grouped around a particular club or sport.                 The problem that meet the organizers of sporting events or recreational activities is the inability to convince sponsors to the effectiveness of promotional activities based on the sport. Inability is due primarily to the fact that companies sponsoring do not use all aspects of the sponsorship and sometimes the club cannot indicate how it should be used. Meanwhile, the lasting effects of sponsorship can bring benefits not only its image but also financial, informational, promotional.                 The primary purpose of the article is to study the effect of the use of the communication by the sponsors local sports clubs. This study will be done by evaluating how the sponsors of these clubs to communicate the fact to support the outside. Space research will be websites of sports clubs from Częstochowa region and information from websites of their sponsors. Article will consist of theoretical and practical parts. In the theoretical part will be presented briefly the most important and latest information on modern forms of communication with the use in companies. The practical part of the study will fill your own.                 During the study it will be verified thesis that sponsors local sports clubs faint attach importance to communicate that fact to potential customers. In this way also it verifies opinion on the effectiveness of sponsorship and lack of ability to use image-supporting local sports clubs. The article is part of a multi-lane testing on the functioning of local sports clubs.